Does Low Skilled Immigration Increase Profits? Evidence from Italian Local Labour Markets - Giorgio Brunello; Elisabetta Lodigiani; Lorenzo Rocco (Institute of Labor Economics (IZA), 2019)
We estimate the (causal) effects of low skill immigration on the performance of Italian manufacturing firms. We find that an increase of the local supply of low skilled immigrants by one thousand units – which corresponds to 8.5 percent of the mean value - raises profits on average by somewhat less than half a percentage point, reduces average labour costs by about 0.1 percent and has no effect on TFP. The positive effects on profits are larger for small firms operating in low tech sectors and for firms located in areas specializing in low skill productions. Our evidence suggests that the recent waves of low skilled immigration in Italy may have hampered the transition to an economic structure characterized by high productivity and wage growth.
Keywords: J61; 330; low skilled immigration; profits; Italy